Subjective Wellbeing in Colombia : Some Insights on Vulnerability, Job Security, and Relative Incomes - Krauss, Alexander; Graham, Carol (World Bank, Washington, DC, 2014)
A burgeoning literature explores the extent to which consumption or income inadequately reflect people's subjective wellbeing, just as GDP at times can provide an incomplete and misleading picture of national wellbeing. Scholars are increasingly using data on subjective wellbeing to complement traditional welfare indicators and to enrich our understanding of wellbeing and quality of life. The paper builds on the present research but it analyzes a much broader, more interdisciplinary, and more policy-relevant range of potential determinants simultaneously than currently existing in the literature on subjective wellbeing. It first analyzes the relative importance of a wide range of characteristics and conditions at the individual, household, regional and macro levels on levels of subjective wellbeing in Colombia in 2010/11; and second, assesses the marginal effects of a number of factors on perceived changes in levels of subjective wellbeing over time for the same respondents from 2008/09 to 2010/11. Findings show that increasing the quality of life of Colombians is largely conditional on minimizing risks and vulnerabilities: reducing the rate and duration of unemployment; improving the delivery of public health services; increasing the share of people with health and pension plans; enhancing safety and security in communities; and reducing levels of discrimination. It finds that job loss has particularly strong effects on levels of satisfaction that are larger than those for increased income, while also controlling for a decrease in income that is often related to being unemployed, suggesting that the human welfare (non-pecuniary) costs of unemployment are driving the strong effects. Moreover, any job, even a low-quality job, is overall better for one's subjective wellbeing than being unemployed. Finally, policy aimed at improving people's subjective wellbeing will likely have the greatest impact if focused on mitigating vulnerabilities and negative shocks that people face.